ANALISIS SWOT UNTUK MENENTUKAN STRATEGI PEMASARAN DAN MENCIPTAKAN COMPETITIVE ADVANTAGES PADA PRODUK SAMBEL PECEL - Maximillian, Stanislaus; Diah Ayu Septi Fauji; Rino Sardanto (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this research is to understand SWOT analysis as a way to determine marketing strategies and create competitive advantages for Mbak Ti's sambel pecel Kediri products. This research was conducted with a descriptive qualitative method using a case study approach. Methods of data collection in the form of interviews and direct observation. Data analysis techniques are SWOT analysis, SWOT matrix, SWOT matrix combination formulation, and internal external matrix. The results show that the product gets a positive score on the analysis of internal and external factors so that it is located in quadrant one which is interpreted as a developing product, prioritizing strategies on developing strengths and exploiting opportunities, the company is well positioned to withstand the pressures generated by the internal and external environment. Based on the research, it can be said that Mbak Ti's sambel pecel product has a competitive advantage that can compete.